The role of digital content in the form of text as travel route information for pokdarwis in wisata Conto Village - Ayuning Wulan (Trigin Publisher, 2023)
This study aims to determine the role of digital content in the form of text as information on travel routes for Pokdarwis in Conto Tourism Village. Using a qualitative approach, where in this study subjective information is in the form of information from tourism stakeholders in Conto Village and a brief history of Conto Tourism Village. Digital content creation training in the form of travel route information texts has an important role for the Conto Tourism Village Pokdarwis as a solution to access constraints to the Soko Langit tourist attraction which must be adapted to the needs of the Pokdarwis. This is done to increase knowledge and skills for tourism stakeholders in the Conto Tourism Village. Besides that, the participation of members of the Conto Tourism Village Pokdarwis plays an important role in the creation of digital content so that the Conto Tourism Village Pokdarwis is able to produce content that displays travel route information. Another thing that is no less important to do is to develop their creativity in creating digital content related to tourism information and marketing in Conto Tourism Village in order to attract more tourist visits